Issues of Using Lesson Study at English Department of Universitas Negeri Padang - Putri Valen Anufri; Yuli Tiarina (Journal of English Language Teaching, 2021)
Lesson study is an alternative program for teacher to see the social interaction of students’ learning process and to stimulus and development learning practices. This research is focused on issues of using Lesson Study at English department in Universitas Negeri Padang. This research population took in the class at English Department Universitas Negeri Padang. This study also sees the lecturer experience about the issue in using Lesson Study the beneficial and difficulties based on the lecturer perspective. This research is conducted by using descriptive research design.  The source of the research were lecturers of English Department Universitas Negeri Padang who have been using Lesson Study in the class. The study shows some issues for lecturers such as time constraints, less understanding of Lesson Study context, campus policy change, and build lecturer’s skills professionally.